Topographical and Physicochemical Contrast in Photopatterned SU-8 Films for Microfabrication of Multilayer Structures - Salazar Alarcón, L.; Martínez,E. D.; Rodríguez, L. M.; Pastoriza, H. (Hindawi, 2016)
Fil: Salazar Alarcón, L. Comisión Nacional de Energía Atómica. Instituto de Nanociencia y Nanotecnología. Laboratorio de Bajas Temperaturas; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina